PRE-TREATMENTS, STRATIFICATION, AND EMERGENCE OF SEEDS OF ILEX PARAGUARIENSIS A.ST.-HIL - Winhelmann, Mara Cíntia; Vargas, Leo Jaime de; Gastmann, Julia; Oliveira, Lucas Massena de; Freitas, Elisete Maria de; Fior, Claudimar Sidnei (Floresta, 2022)
The propagation of yerba mate is carried out by seeds. In nature, birds are the main dispersers and the passage of seeds through the digestive system helps in germination. The laboratory simulation of the conditions provided by the passage of seeds in the digestive tract can be a pre-treatment alternative. Thus, the objective of the work was to evaluate the effect of pre-treatments, associating acid environment in the stratification, on the emergence of I. paraguariensis seeds. Two pre-treatments (PT) were tested: acidified aqueous solution (PT1) and a sequence of aqueous solutions (neutral + acid) (PT2). The pretreated seeds were subjected to stratification in sand (T1 and T2), in addition to seeds without pretreatment that were stratified in sand (T3) and stratified in sand and buried (T4). At 90, 135, and 180 days, seeds were removed from the stratification and taken to the laboratory. In addition to these treatments, a control treatment (seeds without pre-treatment and stratification) and pretreated (PT1 and PT2) seeds without stratification (T5 and T6), which were submitted to emergency and followed up weekly for 180 days, were included. After this period, the tetrazolium test was performed on non-emerged seeds. Seeds stratified for 90 days did not emerge, with 135 days there was 0.9% emergence, and the treatment with stratification in sand and buried (T4) had the greatest emergence (4.25%). With 180 days of stratification, an average emergency of 9.6% was obtained and the highest percentage was seen in T2 (pre-treatment followed by stratification), with 33% of emergence.